Improving Quality of Environmental and Social Impact Assessment Reports: A Statistical Analysis - Omenge, Philip Mangi; Onacha, Gilbert; Were, George; Makindi, Stanley; Nathwani, Jathin (WIT Press, 2022)
Environmental and Social Impact Statement (ESIS) for a proposed development is vital in guiding decision makers arrive at an informed decision. Many studies have analysed ESIS quality using qualitative methods with limited statistical analysis. In this paper, we present findings of a statistical analysis of qualitative data of ESIS using Somers’ delta test (Somers’d). We report on how public participation and analysis of alternatives influence the quality of ESIS. Results show that there is a strong and positive correlation between the quality of ESIS and public participation and also between the quality of ESIS and the analysis of alternatives, which is statistically significant, p < 0.0005, Somers’ d = 0.676 and p < 0.0005, Somers’ d = 0.682, respectively.
Keywords: alternatives analysis; environmental and social impact statements; public participation; Somers’ delta test